The Biological Properties of Bacterial Toxins - M. V. Supotnitskiy (Вестник войск РХБ защиты, 2024)
Knowledge of the biological properties of bacterial toxins is constantly being updated. Over the past two decades, the research interest has shifted from natural toxins to their genetically modified derivatives. The purpose of the work is to summarize the knowledge of the biological properties of bacterial toxins accumulated in the English-language scientific literature in recent years. The research method is analytical. The source base for the research is Englishlanguage scientific literature, accessible through the global Internet. Results. The work examines: the organization and general mechanism of action of bacterial toxin molecules; the reliability of their toxicity indicators given in the scientific literature; toxic effects of toxins of various groups, differing in their mechanism of action; obtaining hybrid and modified toxins; identification of artificial toxins. Conclusions. Among bacterial toxins, binary toxins are the most dangerous. The binary composition of bacterial exotoxins, a good understanding of their subunits, functional domains, assembly mechanisms and intracellular action, make it possible to modify them in the direction of changing the range of targets, toxicity, mechanism of damaging action and immunogenicity. To identify genetically modified toxins, poorly studied analogues and isoforms of natural toxins, special programs based on machine learning can be used.